Being an Author, Corresponding Author, Academic Reviewer and Editor on International Journals: Tips and Tricks - Leunufna, Semuel (European Journal of Applied Sciences, 2023)
Scientific publication is an institutional mission or a main task for a Higher Education Institution yet often negrelected by academics, shown in the lack of number and quality publiacation in Indonesia. Scientific research and publication are beneficial for an academc’s personal career promotion, institutional development including accreditation and ranking, personal and institutional collaborations, improvement in student’s body and therefore financial support for further implementation of three main services (Thri Dharma) of higher education institutions in Indonesia. Publication in the international journal as well as being part of academic reviewer and editorial board enables a wide spread promotion of an academic personal and institution, which may lead to international recognitions and awards. Publication in an indexed journal or journal with impact factor, although requires greater efforts, influence career development through improvement in rank/level, position and maybe structural positions. A number of indexing services/platforms, each with its database are found in their respective internet sites, two, SCOPUS and WoS, claimed to provide greater and modern or older database of literature collections, released their index lists and become the standard quality measurement of journals until recently. For developing countries including Indonesia, a number of constrains may be limiting the involvement of academics in international level.